(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Occlusion of the coronary artery in the rat brought about a progressive rise in kinin levels from control, (before occlusion of the artery), to 30 minutes of the occlusion. The values were 246.38±28.86, 248.75±25.59, 415.23±45.93, and 514.11±41.64pcg/m1 blood for control, pre-occlusion, 15 and 30 minutes after occlusion respectively. Aprotinin (1.52mg/kg body weight) which is a tissue and glandular kallikrein inhibitor, (but not an inhibitor of plasma kallikrein), significantly (p<0.001) prevented the release of kinins. However, Soybean trypsin inhibitor, (SBTI) an inhibitor of kallikrein and other serine proteases, in a dose of 3.03 and 9.1 mg/kg and Hexadimethrine, (which inhibits the activation of plasma pre-kallikrein and Hageman factor and therefore causing inhibition of kinin formation), in doses of 0.091 and 0.91mg/kg, did not prevent the increase in the levels of kinins after the occlusion of the coronary artery for 30 minutes. These results seem to indicate that the tissue kallikrein rather than the plasma kallikrein is involved in the release of kinins during myocardial ischaemia in the rat.